TINJAUAN SEWA BARANG MILIK NEGARA BERDASARKAN PERATURAN MENKEU RI NO. 33/PMK-06/2012 PADA KPKNL BOGOR - Anwar, Yuli (STIE Binaniaga, 2013)
Article 1 Paragraph (1) and Paragraph (2) of Government Regulation 6 of 2006 on the Management of State Property governing is not just a purely administrative, as well as to handle state assets, by improving the efficiency, effectiveness and create added value in managing assets , Therefore, the scope of the management of state assets include demand planning and budgeting; procurement; use; utilization; security and maintenance; assessment; deletion; alienation; administration; coaching, supervision, and control. Utilization of State Property other than land or buildings that are not being used to support the implementation of the basic tasks performed by the user after obtaining the approval of the manager. Utilization of State implemented based on technical considerations with due regard to the interests of the state or region and the public interest. Shapes or patterns of utilization of state property. form: Lease; Borrow and Use; Utilization of cooperation; To wake up Wake Serah Serah and Guna. Considerations for Lease of State Property State Property Rental done to optimize the utilization of state property that has not been or are not utilized in the implementation of the basic tasks and functions of governance, support the implementation of the basic tasks and functions of the ministry or agency, or prevent the use of state property by other parties illegally.Key word: lease of state